2022
DOI: 10.3390/ijms231810211
|View full text |Cite
|
Sign up to set email alerts
|

Biological Mechanisms to Reduce Radioresistance and Increase the Efficacy of Radiotherapy: State of the Art

Abstract: Cancer treatment with ionizing radiation (IR) is a well-established and effective clinical method to fight different types of tumors and is a palliative treatment to cure metastatic stages. Approximately half of all cancer patients undergo radiotherapy (RT) according to clinical protocols that employ two types of ionizing radiation: sparsely IR (i.e., X-rays) and densely IR (i.e., protons). Most cancer cells irradiated with therapeutic doses exhibit radio-induced cytotoxicity in terms of cell proliferation arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 201 publications
0
6
0
Order By: Relevance
“…Published evidences support the hypothesis that saturation of the repair system leads to increasing genomic instability that may contribute to inactivate tumour cells as the dose per fraction is increased beyond the dose range normally studied in vitro. 38,39 Furthermore, some trials indicated that the DNA of cancer cells repairs more slowly and produces also more DNA breaks (single and double) than normal cells, also because various proteins involved in cell death and DNA damage mechanisms decrease the radioresistance of the fast-doubling cancer cells, while increase the radioresistance of slow doubling normal cells. 40 For what concerns the cells radiosensitivity, even whether the underpinning radio-biological mechanisms are not still fully understood, there exists an increasing amount of data at the biochemical level concerning the IR effects due to accelerator-produced charged particles (as protons and heavy ions), but few data concerning the effects due to high-LET beams of fast neutrons.…”
Section: Discussionmentioning
confidence: 99%
“…Published evidences support the hypothesis that saturation of the repair system leads to increasing genomic instability that may contribute to inactivate tumour cells as the dose per fraction is increased beyond the dose range normally studied in vitro. 38,39 Furthermore, some trials indicated that the DNA of cancer cells repairs more slowly and produces also more DNA breaks (single and double) than normal cells, also because various proteins involved in cell death and DNA damage mechanisms decrease the radioresistance of the fast-doubling cancer cells, while increase the radioresistance of slow doubling normal cells. 40 For what concerns the cells radiosensitivity, even whether the underpinning radio-biological mechanisms are not still fully understood, there exists an increasing amount of data at the biochemical level concerning the IR effects due to accelerator-produced charged particles (as protons and heavy ions), but few data concerning the effects due to high-LET beams of fast neutrons.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, radiation is able to significantly increase the staining of C11-BODIPY, lipid peroxidation markers MDA and 4-HNE in cancer cells and tumor samples, indicating that radiation induces lipid peroxidation (Lei et al, 2020a;Zhang et al, 2021a;Zhou et al, 2022). Similarly, irradiated cells exhibit increased expression of the ferroptosis marker gene prostaglandin endoperoxide synthase 2 (PTGS2) (Busato et al, 2022;Yang et al, 2022). Furthermore, Seiji Torii et al shows that knockdown of Arachidonate 15-Lipoxygenase (ALOX15) decreases erastin-induced and RSL3-induced cellular ferroptosis, on the contrary exogenous overexpression of ALOX15 enhances the effects of these compounds.…”
Section: Radiotherapy Induces Ferroptosis By Promoting Lipid Peroxida...mentioning
confidence: 99%
“…Currently, the X-rays used for radiotherapy of EC are low LET rays and cause damage to double-stranded DNA. Biological effects on tumor tissue are limited by factors such as cell cycle and hypoxia, which are unfavorable factors for the treatment of EC 4 . A high-LET carbon ion causes highly complex DNA lesions that include double-strand breaks.…”
Section: Introductionmentioning
confidence: 99%